2006
DOI: 10.1108/00035590610678901
|View full text |Cite
|
Sign up to set email alerts
|

Study of the evolution of a semi‐open cooling circuit

Abstract: PurposeThe evolution of a semi‐open cooling circuit of a nuclear reactor was monitored over a two year period. The work aims to provide orientation elements for preventive procedures against localised corrosion.Design/methodology/approachThe water of the circuit was analysed in stagnation and in circulation, at various sampling points. The rust was analysed by neutron diffraction and the surface quality of the steel was checked by microscopic observations.FindingsThe obtained results did not confirm the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 15 publications
(18 reference statements)
0
8
0
Order By: Relevance
“…In a previous paper, it was shown that for materials used in an open cooling circuit, the choice of the carbon content of steel should take into account the chloride quantity of the medium to which it will be exposed (Boucherit and Tebbib, 2005). Even if the steel does not exhibit localised attack after several years (Boucherit et al , 2006), preventive measures must be considered because localised corrosion occurs rapidly and insidiously at a microscopic level, and can be stimulated by numerous thermohydraulic factors.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous paper, it was shown that for materials used in an open cooling circuit, the choice of the carbon content of steel should take into account the chloride quantity of the medium to which it will be exposed (Boucherit and Tebbib, 2005). Even if the steel does not exhibit localised attack after several years (Boucherit et al , 2006), preventive measures must be considered because localised corrosion occurs rapidly and insidiously at a microscopic level, and can be stimulated by numerous thermohydraulic factors.…”
Section: Introductionmentioning
confidence: 99%
“…Then we used the collected electrochemical data to evaluate different artificial neural network structures. All electrochemical experiments were carried out with the same material: a 0.2 per cent carbon steel used in the secondary cooling circuit of a nuclear installation (Boucherit et al , 2006). The preparation of the metal samples for the electrochemical experiments is detailed in a previous publication (Boucherit and Tebib, 2005).…”
Section: Methodsmentioning
confidence: 99%
“…This work is part of a research programme on the behaviour of localized corrosion of carbon steel used in the secondary cooling circuit of a nuclear reactor (Boucherit et al, 2006). The work is based on gathering experimental data obtained through electrochemical measurements.…”
Section: Introductionmentioning
confidence: 99%